Comparison of Herbal Medicines Used for Women’s Menstruation Diseases in Different Areas of the World - Jiao, Majing; Liu, Xinqiao; Ren, Yongshen; Wang, Yingzhou; Cheng, Long; Liang, Yunhui; Li, Yanqiu; Zhang, Tianpei; Wang, Wen; Mei, Zhinan (Frontiers in Pharmacology, 2022)
Aims: This review aims to compare the use of herbal medicine used to treat women’s menstruation and the prevalence of menstrual diseases in different regions, which reveal the use of herbal medicine globally and provide scientific guidance for improving women’s health. Materials and methods: The information available on herbal medicines for women between the years 2000 and 2021 was systematically collected via the library and electronic search systems such as Google Scholar, PubMed, ScienceDirect, and Web of Science as well as secondary resources including books and conference proceedings. Results: Totally, 571 ethnic medicines commonly used for women’s menstruation health in Asia, Europe, Oceania, Africa, and America were accounted. Zingiber officinale Roscoe (Ginger), Ruta graveolens L. (Common rue), Angelica sinensis (Oliv.) Diels (Angelica sinensis), Foeniculum vulgare Mill. (Fennel), Catharanthus roseus (L.) G. Don (Catharanthus roseus) and other medicines which have obvious advantages and long-term usage are utilized in the treatment of menstrual diseases. Family Asteraceae, Lamiaceae, Apiaceae, Fabaceae, and Zingiberaceae are the most common medicinal plant families used for such treatments. In many instances, the application of fresh parts of plants was observed because of the healers’ belief regarding the higher efficiency of the medicine made from fresh plants. Edible plants are used in a wide range of countries. Conclusions: Women’s menstruation health is directly related to their health condition. Traditional medicines of most ethnic groups have contributed to women’s health care and treatment of gynecological diseases. Practitioners in this field have gained elaborate experience in treatments and medication, and assembled a large number of effective drugs and prescriptions. These experiences have also been inherited and developed by modern clinical application and scientific research. However, the basic research on these drugs is not sufficient, the knowledge of drug use has not been fully popularized, the advantages of drugs have not been fully utilized, and the guiding potential to modern drug research continues to be insufficient. As such, it is necessary to further promote and make a significant contribution to women’s health.